Metodologi Kitab Tafsir Rabbana Min Kalami Rabbina Karya Moh. Abdul Khaliq Hasan (Studi Analisis Wacana) - Harjanti, Chikmatul Aprilia; Hasan, Moh Abdul Kholiq (Jawa Timur: Prodi. Ilmu Al Quran dan Tafsir Fakultas Ushuluddin IAI Tarbiyatut Tholabah, 2024)
Tafsir Rabbana Min Kalami Rabbina has two interesting approaches to study, namely psychological and historical approaches and contains more than 100 references. This research aims to reveal the factors behind the birth of Tafsir Rabbana Min Kalami Rabbina and analyze the discourse contained in it. This research uses descriptive-qualitative approach with discourse analysis method. The research data was obtained from the text of the tafsir book. The results of the analysis show that the book of Tafsir Rabbana Min Kalami Rabbina was born from Moh Abdul Kholiq Hasan's initiative to compile thematic interpretations of prayer verses. Discourse analysis reveals that Moh Abdul Kholiq Hasan was influenced by Nashruddin al-Baidawi's tafsir method in terms of approach, style, and writing systematics. In addition, the author's scientific background and social context also contribute significantly to the formation of this tafsir discourse. Overall, this study concludes that the book of Tafsir Rabbana Min Kalami Rabbina by Moh Abdul Kholiq Hasan is a unique work of tafsir, which combines scientific and cultural aspects in an effort to understand the meaning of the verses of the Qur'an.